The double-edged role of hydrogen sulfide in the pathomechanism of multiple liver diseases - Liu, Bihan; Wang, Shanshan; Xu, Ming; Ma, Yanan; Sun, Rui; Ding, Huiguo; Li, Lei (Frontiers in Pharmacology, 2022)
In mammalian systems, hydrogen sulfide (H2S)—one of three known gaseous signaling molecules in mammals has been found to have a variety of physiological functions. Existing studies have demonstrated that endogenous H2S is produced through enzymatic and nonenzymatic pathways. The liver is the body's largest solid organ and is essential for H2S synthesis and elimination. Mounting evidence suggests H2S has essential roles in various aspects of liver physiological processes and pathological conditions, such as non-alcoholic fatty liver disease, liver fibrosis, liver ischemia‒reperfusion injury, hepatocellular carcinoma, hepatotoxicity and acute liver failure. In this review, we discuss the functions and underlying molecular mechanism of H2S in multiple liver pathophysiological conditions.